Alpha-Fetoprotein and its Receptor: More Than Oncofoetal Antigens. - N Pak, Vladimir (Journal of Cancer Genetics And Biomarkers, 2019)
This review revisits alpha‑fetoprotein (AFP) and AFP receptor biology beyond their classic role as oncofetal markers. It summarizes signaling, tumor biology, and clinical implications across malignancies, including diagnostic, prognostic, and therapeutic angles. The authors highlight opportunities and limitations for AFP‑targeted interventions.
Keywords: alpha-fetoprotein receptor; oncofetal antigens; myeloid-derived suppressor cells; cancer; immunotherapy.